2002
DOI: 10.1289/ehp.02110583
|View full text |Cite
|
Sign up to set email alerts
|

Host and environmental determinants of polychlorinated aromatic hydrocarbons in serum of adolescents.

Abstract: This study investigated host factors and environmental factors as potential determinants of polychlorinated aromatic hydrocarbons (PCAHs) in serum of adolescents. We recruited 200 participants (80 boys and 120 girls), with a mean age of 17.4 years (SD, 0.8), in Belgium from a rural control area (Peer) and from two polluted suburbs of Antwerp where a nonferrous smelter (Hoboken) and waste incinerators (Wilrijk) are located. We quantified polychlorinated biphenyls (PCBs; congeners 138, 153, and 180) in serum by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 38 publications
2
31
2
Order By: Relevance
“…That different mechanism predominate in adults compared to adolescents seems likely The quite strong negative associations in adolescents between organochlorines and BMI observed previously by Nawrot et al (2002) and, for organochlorines other than PCB118, also in this study, are contrasting with the positive associations with BMI found for HCB, PCB 118 and p,p'-DDE in both adult men and women and, for men, also for dioxin-like activity. The negative associations observed in adolescents can probably be explained partly by a transient dilution effect in adipose tissue during growth as proposed by Nawrot et al (2002). However, a dilution effect cannot explain the positive associations observed in adolescents between PCB118 and BMI after adjustment for other exposures, nor why the association between BMI and organochlorine pollutants was in all cases stronger at exposures below the median than at exposures above the median.…”
Section: Discussioncontrasting
confidence: 87%
“…That different mechanism predominate in adults compared to adolescents seems likely The quite strong negative associations in adolescents between organochlorines and BMI observed previously by Nawrot et al (2002) and, for organochlorines other than PCB118, also in this study, are contrasting with the positive associations with BMI found for HCB, PCB 118 and p,p'-DDE in both adult men and women and, for men, also for dioxin-like activity. The negative associations observed in adolescents can probably be explained partly by a transient dilution effect in adipose tissue during growth as proposed by Nawrot et al (2002). However, a dilution effect cannot explain the positive associations observed in adolescents between PCB118 and BMI after adjustment for other exposures, nor why the association between BMI and organochlorine pollutants was in all cases stronger at exposures below the median than at exposures above the median.…”
Section: Discussioncontrasting
confidence: 87%
“…The AhR-chemical-activatedluciferase-expression (AhR-CALUX) bioassay can measure the activity of pure compounds (21,23) as well as the integrated activity of total DLCs, and thus the net AhR-TEQ of complex mixtures as found in bovine and human milk (24,25), and human serum and follicular fluid (17,(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…In the body, organochlorine compounds reside mainly in adipose (80%), with rapid, passive distribution to blood and other tissues proportional to their neutral lipid content. Yet, body mass index (BMI; weight in kg divided by height in meters squared), a surrogate for adiposity, exhibits both positive and negative correlations with organochlorine compound levels in cross-sectional studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). On the other hand, reported relationships between BMI and elimination rate (expressed as rate constants or half-life) are consistently positive, such that a higher BMI results in a longer half-life (13,15,(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%